2016
DOI: 10.1371/journal.pntd.0004783
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Rift Valley Fever in Mayotte: Insights and Perspectives from 11 Years of Data

Abstract: Rift Valley fever (RVF) is a zoonotic arboviral disease that is a threat to human health, animal health and production, mainly in Sub-Saharan Africa. RVF virus dynamics have been poorly studied due to data scarcity. On the island of Mayotte in the Indian Ocean, off the Southeastern African coast, RVF has been present since at least 2004. Several retrospective and prospective serological surveys in livestock have been conducted over eleven years (2004–15). These data are collated and presented here. Temporal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 22 publications
1
54
0
Order By: Relevance
“…In Maputo Province, an overall seroprevalence of 36.9% was documented in cattle (8). The results indicated the possible circulation of RVF virus during interepidemic periods without the manifestation of typical clinical signs, as has been described elsewhere (9).…”
Section: R Ift Valley Fever (Rvf) Virus (Family Bunyaviridaesupporting
confidence: 77%
“…In Maputo Province, an overall seroprevalence of 36.9% was documented in cattle (8). The results indicated the possible circulation of RVF virus during interepidemic periods without the manifestation of typical clinical signs, as has been described elsewhere (9).…”
Section: R Ift Valley Fever (Rvf) Virus (Family Bunyaviridaesupporting
confidence: 77%
“…Such a discrepancy is likely to result from space scale sampling differences: our estimation was done at the eco-regional level whereas the other one was performed in a district highly affected by RVF in 20081219. Two studies performed in the tropical islands of the South-West Indian Ocean showed an annual RVFV antibody acquisition about 17.5% in Union of Comoros in 2010–1143 and an IgM prevalence about 4% in 2010–11 in Mayotte44, which were higher than our estimations. Yet, the climatic situations in the Union of Comoros and Mayotte, under marine tropical conditions, are extremely different than in Madagascar.…”
Section: Discussionmentioning
confidence: 96%
“…Cattle production is extensive, with a population size of about 17,000 heads. Several vector‐borne cattle diseases have been reported on the island over the past decade, including Rift Valley fever, bluetongue and epizootic haemorrhagic disease (Dommergues et al., ; Métras et al., ). In addition, due to its proximity and close connection to its neighbouring areas through active trade and human immigration, Mayotte has experienced several introductions of other arboviruses, such as dengue or chikungunya viruses (Tortosa et al., ).…”
Section: Introductionmentioning
confidence: 99%